PENGEMBANGAN ASESMEN FORMATIF TWO-TIER MULTIPLE CHOICE BERBASIS HOTS MELALUI MEDIA QUIZIZZ PADA MATERI BANGUN DATAR KELAS IV SEKOLAH DASAR - Sahwitri Agustin, Vivi; Gusmaulia Eka Putri, Andi; Destrinelli, Destrinelli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a two-tier multiple-choice formative assessment based on Higher Order Thinking Skills (HOTS) through Quizizz media on flat shape materials for Grade IV elementary school students. The background of this study is the limitation of teachers in designing formative assessment instruments capable of measuring students' higher-order thinking skills, as well as the suboptimal use of technology in mathematics learning evaluation activities. The type of research used is research and development (R&D) using the ADDIE model, which includes the stages of Analyze, Design, Develop, Implement, and Evaluate. The research subjects are Grade IV students of SDN 14/I Sungai Baung. Data collection instruments include interviews, validation questionnaires from material experts, language experts, and media experts, as well as documentation. Data analysis techniques are carried out both quantitatively and qualitatively. The research results show that the HOTS-based two-tier multiple choice formative assessment through the Quizizz media developed has a very good level of validity and reliability, making it feasible to use as a learning evaluation instrument for mathematics on flat shape material. This assessment is expected to help teachers identify students' understanding and thinking processes, as well as train students' critical and analytical thinking skills more optimally.